STUDI INTERAKSI DINAMIK NON-LINIER TETHER-HULL - Elvira
In dynamic analysis of a hull, an uncoupled analysis method is usually used for purpose of simplification. This method is performed without regarding dynamic of the tether. It is conducted by assuming the tether as a linear massless spring. For a deeper water, effect of tether dynamic is much more influencing. The existing of current, for example, is causing a larger deformation of the tether, especially if the given tension is not sufficient to keep the tether in linear condition. This is the main reason of why the dynamic of tether is to be included in analysis. This method is generally known as a coupled analysis. Evaluation of the assumptions taken in derivation of finite element stiffness matrix - small deflection theory - also need to be done. The main purpose of this research is to analyze the difference between uncoupled and coupled results in some variations of initial tension of the tether dan current. It is also aimed to see some differences of large deformation theory (nonlinear tether stiffness) and small deformation theory (linear tether stiffness) results.